Tundra Type Drives Distinct Trajectories of Functional and Taxonomic Composition of Arctic Fungal Communities in Response to Climate Change – Results From Long-Term Experimental Summer Warming and Increased Snow Depth - Geml, József; Morgado, Luis N.; Semenova-Nelsen, Tatiana A. (Frontiers in Microbiology, 2021)
The arctic tundra is on the brink of significant changes and there are serious concerns related to the future of arctic biodiversity because of the threats represented by climate change scenarios. Arctic land surface temperatures and precipitation are predicted to increase further, likely causing major changes in terrestrial ecosystems. As a response to warming temperatures, shifts in vegetation and soil fungal communities have already been observed. Little is known, however, how long-term experimental warming coupled with increased snow depth influence the trajectories of soil fungal communities in different tundra types. We compared fungal community composition in experimental plots simulating the expected increase in summer warming and winter snow depth, based on DNA metabarcoding data. Fungal communities in the sampled dry and moist acidic tundra communities differed greatly, with tundra type explaining ca. one-third of compositional variation. Furthermore, dry and moist tundra appear to have different trajectories in response to climate change. Specifically, while both warming and increased snow depth had significant effects on fungal community composition in dry tundra, the effect of increased snow was greater. However, in most tundra, fungal communities mainly were affected by summer warming, while increased snow depth had a smaller effect and only on some functional groups. In dry tundra, microorganisms generally are limited by moisture in the summer and extremely low temperatures in winter, which is in agreement with the stronger effect of increased snow depth relative to warming. On the contrary, moist tundra soils generally are saturated with water and show small fluctuations in temperature, which is conducive to the greater effect of warming on resident microbes.